Vaginal Birth after Two Previous Cesarean Sections versus Elective Repeated Cesarean: A Retrospective Study - De Leo, Rossella; La Gamba, Domenico Antonio; Manzoni, Paolo; De Lorenzi, Raffaella; Torresan, Sonia; Franchi, Massimo; Uccella, Stefano (American Journal of Perinatology, 2020)
Objective Trial of labor after cesarean delivery (TOLAC) is a common practice worldwide but the evidence is still scant regarding this practice in women who underwent 2 previous cesareans. The purpose of this study is to retrospectively review our experience with vaginal birth after two previous cesarean sections (VBA2C), with specific attention to the indications for previous cesarean and to the women's motivation for attempting trial of labor.Study Design This was a retrospective cohort study conducted in a primary care hospital between January 2011 and December 2019. Inclusion criteria were: singleton pregnancies, absence of morphological abnormalities at ultrasonographic screening of the second trimester (or at any other stage of pregnancy), and two previous cesarean sections.Results The final analysis included 114 cases for maternal and neonatal outcomes. In total, 40.4% of women chose trial of labor after two cesarean delivery (TOLA2C group). TOLA2C was associated with a success rate of 76.1%, a higher gestational age at birth, and a shorter hospital stay, compared with elective repeated cesarean delivery group. There were no significant differences in the rate of Apgar scores at 5 minutes <7 between both groups. The percentage of successful TOLA2C in women with prior vaginal delivery was 92.8%. Factors related to failed TOLA2C included failure to progress (3/11, 27.3%), nonreassuring fetal heart rate (3/11, 27.3%), and no onset of spontaneous labor after premature rupture of membranes (5/11, 45.4%). In the group of TOLA2C, more than 70% accepted to travel more than 45 minutes to reach our hospital, with the aim to attempt VBA2C.Conclusion TOLA2C is a possible option for both mothers and neonates in selected cases. Adequate counseling about pros and cons of TOLA2C is mandatory. The woman's motivation represents a key element to determine the success of VBA2C.Key Points
Keywords: vaginal birth after cesarean; trial of labor; uterine rupture; elective repeated cesarean delivery